Strategi Public Relations Pemprov Bali Menuju Bali Bebas Sampah Plastik - I Komang Agus Widiantara (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
The handling of plastic waste in Bali was taken seriously by the Provincial Government (Pemprov) with the issuance of Bali Governor Regulation No.97 / 2018 concerning Limitation on the Occurrence of Disposable Plastic Waste. This regulation is a solution amid the complicated problems of waste on the island. After the enactment of these rules, various elements of society, environmental activists and communities welcomed positively. The movement to fight plastic waste until the campaign to cut the use of plastic elements is well socialized. By reviewing qualitatively, this research tries to outline the public relations strategy used by the Bali Provincial Government towards a plastic-free Bali. From the studies conducted, the strategic approach adopted in optimizing the role of public relations includes: publications, new events, and community involvement. Including the crisis handling efforts after the adoption of the Governor Regulation which resulted in the review of the injured party through the Asung Court (MA) such as a defensive, adaptive and dynamic strategy.